A mutational comparison of adult and adolescent and young adult (AYA) colon cancer. Issue 5 (30th November 2017) - Tricoli, James V.; Boardman, Lisa A.; Patidar, Rajesh; Sindiri, Sivasish; Jang, Jin S.; Walsh, William D.; McGregor, Paul M.; Camalier, Corinne E.; Mehaffey, Michele G.; Furman, Wayne L.; Bahrami, Armita; Williams, P. Mickey; et al.
Abstract : BACKGROUND: It is possible that the relative lack of progress in treatment outcomes among adolescent and young adult (AYA) patients with cancer is caused by a difference in disease biology compared with the corresponding diseases in younger and older individuals. There is evidence that colon cancer is more aggressive and has a poorer prognosis in AYA patients than in older adult patients. METHODS: To further understand the molecular basis for this difference, whole‐exome sequencing was conducted on a cohort of 30 adult, 30 AYA, and 2 pediatric colon cancers. RESULTS: A statistically significant difference in mutational frequency was observed between AYA and adult samples in 43 genes, including ROBO1, MYC binding protein 2 ( MYCBP2 ), breast cancer 2 (early onset) ( BRCA2 ), MAP3K3, MCPH1, RASGRP3, PTCH1, RAD9B, CTNND1, ATM, NF1 ; KIT, PTEN, and FBXW7 . Many of these mutations were nonsynonymous, missense, stop‐gain, or frameshift mutations that were damaging. Next, RNA sequencing was performed on a subset of the samples to confirm the mutations identified by exome sequencing. This confirmation study verified the presence of a significantly greater frequency of damaging mutations in AYA compared with adult colon cancers for 5 of the 43 genes ( MYCBP2, BRCA2, PHLPP1, TOPORS, and ATR ). CONCLUSIONS: The current results provide the rationale for a more comprehensive study with a larger sample set and experimental validation of the functional impact of the identified variants along with their contribution to the biologic and clinical characteristics of AYA colon cancer. Cancer 2018;124:1070‐82. © 2017 American Cancer Society . Abstract : Mutational differences are detected between adolescents and young adults with colon cancer compared with their adult counterparts. The MYC binding protein 2 and breast cancer 2 (early onset) genes are frequently mutated in adolescent and young adult patients who have colon cancer.